Occupational Radiation Exposure Estimated for Fusion Demonstration Reactors and Beyond. (17th February 2022) - Guo, Dingqing; Chen, Chao; Wang, Zhen; Lin, Jian; Zhang, Bing; Ge, Daochuan; Chen, Zhibin
Abstract: The fusion reactor fueled by deuterium and tritium will generate many neutron activation products, causing occupational exposure and radiation risk. The minimization of occupational radiation exposure (ORE) is one of the safety goals for fusion reactors. However, detailed designs and management schemes are still lacking for fusion reactors, and the ORE evaluations are still well simplified. In this paper, an integrated assessment approach is proposed for fusion reactors at the conceptual or detailed design stage. The core idea is to estimate the ORE by referring to the dose rates and work efforts of mature fission reactors and ITER and modifying the data of these similar systems by a proportional coefficient according to the differences of component scale, operating environment, etc. The results showed that water cooling fusion reactors will generate the highest collective dose of 2635 p-mSv/year, while the PbLi cooling ones come next with about 1684 p-mSv/year and the helium cooling ones are the least. This method will contribute to fusion reactor design, operation, and maintenance optimization at the earlier stages and provide guidance to reduce the overall potential ORE to workers.